2016
DOI: 10.1002/ana.24716
|View full text |Cite
|
Sign up to set email alerts
|

Seed‐competent high‐molecular‐weight tau species accumulates in the cerebrospinal fluid of Alzheimer's disease mouse model and human patients

Abstract: Objective Cerebrospinal fluid (CSF) tau is an excellent surrogate marker for assessing neuropathological changes that occur in Alzheimer's disease (AD) patients. However, whether the elevated tau in AD CSF is just a marker of neurodegeneration or in fact a part of the disease process is uncertain. Moreover, it is unknown how CSF tau relates to the recently described soluble high-molecular-weight (HMW) species that is found in postmortem AD brain and can be taken up by neurons and seed aggregates. Methods We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
101
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 94 publications
(111 citation statements)
references
References 30 publications
(77 reference statements)
7
101
0
Order By: Relevance
“…Recent studies showed that a lot of the tau detected in cerebrospinal fluid from AD patients has a molecular weight similar to dimeric and oligomeric of truncated tau, at least as determined by size exclusion (Takeda et al . ); similar low‐molecular weight tau derived from rTg4510 mouse brain lysates did not support the aggregation of TauRDP301S in a cell assay designed to sensitively detect tau aggregation (Takeda et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies showed that a lot of the tau detected in cerebrospinal fluid from AD patients has a molecular weight similar to dimeric and oligomeric of truncated tau, at least as determined by size exclusion (Takeda et al . ); similar low‐molecular weight tau derived from rTg4510 mouse brain lysates did not support the aggregation of TauRDP301S in a cell assay designed to sensitively detect tau aggregation (Takeda et al . ).…”
Section: Resultsmentioning
confidence: 99%
“…Many forms of tau have been observed to be secreted in vitro including phosphorylated tau (Pooler, Phillips, et al, ; Saman et al, ) and C‐terminally truncated tau (Kanmert et al, ). Recent data from AD cerebrospinal fluid and brain samples indicates that high molecular weight tau species may be released from human neurons and are competent to induce tau seeding in cultured cells (Takeda et al, ). Several mechanisms of tau release have been proposed (reviewed by (Wang & Mandelkow, )) including exocytosis of tau, vesicle mediated release such as in exosomes (Saman et al, ), or synaptic vesicle release (Polanco, Scicluna, Hill, & Gotz, ).…”
Section: Discussionmentioning
confidence: 99%
“…In the CSF of AD patients and transgenic mice expressing human-type tau, seed-competent tau is present that can stimulate tauopathy in cultured cells (Takeda et al, 2016), and some tau seeds in AD CSF appear to be associated with extracellular vesicles (Wang et al, 2017). The seeding capability of CSF tau in vivo , however, has not been reported; because CSF Aβ does not readily seed plaques or CAA in APP-transgenic mice (Fritschi et al, 2014b) (see above), a similar analysis of in vivo tau seeding by CSF from patients with AD (and other tauopathies) in the appropriate models could be informative.…”
Section: The Prion-like Properties Of Aggregated Taumentioning
confidence: 99%